URGENSI PEMBENTUKAN KITAB UNDANG-UNDANG HU- KUM EKONOMI SYARIAH INDONESIA - Pratiwi, Pratiwi; Rifai, Ahmad (Journal of Islamic Law Studies, 2018)
The development of Islamic Economic Financial in Indonesia was growing rapidly in Indonesia since the last ten years (2000-2010). This development is almost happen in all Islamic economic financial institution. However, its development not be accomodated by the regulation, even though since 2008 Indonesian’s Supreme Court trough Indonesian Supreme Court regulation (PERMA) Number 2 year of 2008 assigned The Compilation of Islamic Economy Law. The position of its regulation in hier- archy of Indonesia regulations is considered has not strong position. In other hand, the demand of Islamic economy law is high. Therefore, it needs to create The Codification of Islamic Economy Law in Indonesia as a cover of implementation of sharia principle. In this research, the authors use qual- itative approach within normative juristical with library research to analysis the potion’s of KHES based on Indonesian Law Number 12 Year of 2011 about The Formation of Regulations.